Mortality outcomes in patients transfused with fresher versus older red blood cells: a meta‐analysis. Issue 3 (20th February 2017) - Chai‐Adisaksopha, C.; Alexander, P. E.; Guyatt, G.; Crowther, M. A.; Heddle, N. M.; Devereaux, P. J.; Ellis, M.; Roxby, D.; Sessler, D. I.; Eikelboom, J. W.
Abstract : Background: Among transfused patients, the effect of the duration of red blood cell storage on mortality remains unclear. This study aims to compare the mortality of patients who were transfused with fresher versus older red blood cells. Methods: We performed an updated systematic search in the CENTRAL, MEDLINE, EMBASE and CINAHL databases, from January 2015 to October 2016. RCTs of hospitalized patients of any age comparing transfusion of fresher versus older red blood cells were eligible. We used a random‐effects model to calculate pooled risk ratios (RRs) with corresponding 95% confidence interval (CI). Results: We identified 14 randomized trials that enrolled 26 374 participants. All‐cause mortality occurred in 1219 of 9531 (12·8%) patients who received a transfusion of fresher red blood cells and 1810 of 16 843 (10·7%) in those who received older red blood cells (RR: 1·04, 95% CI: 0·98–1·12, P = 0·90, I 2 = 0%, high certainty for ruling out benefit of fresh blood, moderate certainty for ruling out harm of fresh blood). In six studies, in‐hospital death occurred in 691 of 7479 (9·2%) patients receiving fresher red cells and 1291 of 14 757 (8·8%) receiving older red cells (RR: 1·06, 95% CI: 0·97–1·15, P = 0·81, I 2 = 0%, high certainty for ruling out benefit of fresh blood, moderate certainty for ruling out harm of fresh blood). Conclusion: Transfusion of fresher red blood cells does not reduce overall or in‐hospital mortality when compared with older red blood cells. Our results support the practice of transfusing patients with the oldest red blood cells available in the blood bank.